Evaluation of the current practices on slaughterhouses in the Eastern District of Aklan. - Andrade, Cekyna Grace
Concerns on quality and safety of meat products have been growing over the years. For both ethical and meat quality reasons, consumers have given more attention and concern to the welfare of the slaughtered animals and the conditions it experiences prior to slaughter. With this, evaluation of both the facility and the pig slaughter practices of the slaughterhouses that supply and produce meat for consumption was conducted. The study focused on the current pre-slaughter to post-slaughter practices of slaughterhouses in the Eastern district of Aklan province. Through a survey, observation, and documentation, the common practices of these slaughterhouses in different slaughter operations were determined. Results revealed the frequency of the respondents who answered always, sometimes, never, or no answer in the survey questionnaire. It was observed that in terms of physical structure, most of the slaughterhouses have shown poor qualities. Cracked floors, stained walls, unclean ceilings, and lack of several facilities including storage, handwashing, dressing room, and holding area for the meat, were observed which needs improvement and further development. Moreover, it was noticed that the self-reported data from the respondents and actual observation of the researcher on most of the practices (e.g., personal hygiene, animal welfare, pig slaughtering, handling of the offal, and handling and storage of the meat) were contradictory. Results showed that several practices, particularly: personal hygiene, the slaughter of the animal, use of non-potable water, unhygienic handling of the offal, as well as the sub-standard practice during post-slaughter activities can be the possible sources of contamination, which may compromise the quality and safety of the meat (pork). Therefore, efforts to comply with standards are needed from the slaughterhouse. Strict and proper implementation of the standard practices must be assessed and constantly monitored by the Local Government Unit to ensure compliance from the slaughterhouses.